Are interventions focused on gender-norms effective in preventing domestic violence against women in low and lower-middle income countries? A systematic review and meta-analysis - Agumasie Semahegn; Kwasi Torpey; Abubakar Manu; Nega Assefa; Gezahegn Tesfaye; Augustine Ankomah (BMC, 2019)
Abstract Background One in three women experience intimate partner violence worldwide, according to many primary studies. However, systematic review and meta-analysis of intimate partner violence is very limited. Therefore, we set to summarize the findings of existing primary studies to generate evidence for informed decisions to tackle domestic violence against women in low and lower-middle income countries. Methods Studies were searched from main databases (Medline via PubMed, EMBASE, CINAHL, PopLine and Web of Science), Google scholar and other relevant sources using electronic and manual techniques. Published and unpublished studies written in English and conducted among women aged (15-49 years) from 1994 to 2017 were eligible. Data were extracted independently by two authors, and recorded in Microsoft Excel sheet. Heterogeneity between included studies was assessed using I2, and publication bias was explored using visual inspection of funnel plot. Statistical analysis was carried out to determine the pooled prevalence using Comprehensive Meta-Analysis software. In addition, sub-group analysis was carried out by study-setting and types of intimate partner violence. Results Fifty two studies were included in the systematic review. Of these, 33 studies were included in the meta-analysis. The pooled prevalence of lifetime intimate partner violence was 55% (95% CI: 52, 59%). Of these, main categories were lifetime physical violence [39% (95% CI: 33, 45%); psychological violence [45% (95% CI: 40, 52%)] and sexual violence [20% (95% CI: 17, 23%)]. Furthermore, the pooled prevalence of current intimate partner violence was 38% (95% CI: 34, 43%). Of these, physical violence [25% (95% CI: 21, 28%)]; psychological violence [30% (95% CI: 24, 36%)] and sexual violence [7.0% (95% CI: 6.6, 7.5%)] were the pooled prevalence for the major types of intimate partner violence. In addition, concurrent intimate partner violence was 13% (95% CI: 12, 15%). Individual, relationship, community and societal level factors were associated with intimate partner violence. Traditional community gender-norm transformation, stakeholders' engagement, women's empowerment, intervention integration and policy/legal framework were highly recommended interventions to prevent intimate partner violence. Conclusion Lifetime and current intimate partner violence is common and unacceptably high. Therefore, concerned bodies will need to design and implement strategies to transform traditional gender norms, engage stakeholders, empower women and integrate service to prevent violence against women. Protocol registration PROSPERO: 2017: CRD42017079977.